P3.418 Factors Associated with Condom Breakage Among Men Who Have Sex with Men in India. (13th July 2013) - Ramesh, S; Mehrotra, P; Ganju, D
Abstract : Background: Condom use has long been identified as one of the most effective means of preventing HIV/STI. However recent studies among female sex workers suggest high rates of condom breakage. There is paucity of evidence on the extent of condom breakage, its association with the prevalence of HIV/STI and the factors associated with condom breakage among men who have sex with men (MSM). Methods: Data were drawn from a cross-sectional bio-behavioural survey of 3806 self-identified MSM from three high prevalence states of India, recruited through probability based sampling in 2009–10. Logistic regression models were used to examine the association between condom breakage and the prevalence of HIV/STI and to identify the correlates of condom breakage. Results: Overall, 20% of MSM reported condom breakage in the month prior to the survey. Condom breakage was associated with increased odds of HIV/STI. Additionally, no significant difference in the prevalence of HIV/STI was observed between MSM who were inconsistent condom users and MSM who used condoms at every sexual encounter but reported condom breakage.MSM who were 25–34 years old; were predominantly receptive sexual partner; travelled outside their current place of residence and had sex at destination; consumed alcohol in the month prior to the survey; reported drug use (self or partner); had same sex sexual debut at a younger age and used oil based lubricant were significantly more likely to report condom breakage compared to their counterparts. Conclusion: Condom breakage was common among MSM in this study. Interventions with MSM in India which focus primarily on consistent condom use should also consider the threat posed by condom breakage. Special effort is required to provide information on correct condom use to MSM at higher risk of experiencing condom breakage.